Allelopathy and phytotoxicity of Zanthoxylum rhoifolium lam - Silva, R. M.G. [UNESP]; Livio, A. A. [UNESP]; Santos, V. H.M. [UNESP]; Mecina, G. F. [UNESP]; Silva, L. P. [UNESP] (My University, 2012)
In Cerrado, Zanthoxylum rhoifolium Lam. stands out because it interferes with the growth and development of other plants. The preliminary phytochemical analyses showed the presence of polyphenols and flavonoids. The Z. rhoifolium extract inhibited the germination index (5 mg mL-1=0.5%; 10mg mL-1=37.5% and 20mg mL-1=85.5%) decreased the germination and the lettuce seedlings growth (roots and the hypocotyls) and reduced the mitotic index than control. The extract of 1000 μg mL-1conc contained (165.20 mg and 45.74 mg, phenols and total flavonoids, respectively) and had higher antioxidant activity (80.52%). We concluded that Z. rhofolium possesses allelopathic potential.
Keywords: Allelochemicals; Allelopathy; Antioxidant activity; Flavonoids; Lactuca sativa; Lettuce; Mitotic index; Phenols; Phytotoxicity; Zanthoxylum rhoifolium